A Unique and Rare Presentation of Obstructed Choledochal Cyst in an Adult: A Case Report - Ahmad E. Al-Mulla; Salah Termos; Fawzia Ashkanani; Ehab S. Imam; Abdulla E. Sultan; Ali Altabeekh; Mohammad Y. Saleh; Ahmad Al-Jafar (Surgical Research – Open Journal, 2021)
Choledochal cysts in adults are rare congenital abnormalities. Approximately 80% are found in childhood. Thus, their presentation in adults is always associated with complications, such as stone formation, inflammation and malignancies. The pathophysiology of this disease is yet uncertain. There are different types of choledochal cysts. Diagnosis can be challenging clinically; however, imaging techniques, such as ultrasound, magnetic resonance cholangiopancreatography (MRCP) and computed tomography (CT), can be helpful. We found several procedures performed in the extant literature, such as choledochoduodenostomy and choledochojejunostomy submucosal excision of the cyst; however, the best surgical option is excision with hepaticojejunostomy. We discuss the unusual presentation of a 33-year-old female patient with an obstructed choledochal cyst, despite having undergone a drainage procedure in childhood.